ANALYSIS OF THE EFFECT OF MARKET RATIO AND MARKET INFORMATION ON STOCK RETURNS (Case Study of Food and Beverage Industry Sub-Sector Companies Listed on the Indonesia Stock Exchange for the Period 2019-2021) - Nuraulia, Naifah; Yunita, Irni (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Stock return is one of the motivations for investors to invest. When investing, investors must analyze various sources, such as financial reports, and be aware of market information that can enrich their decision-making process. This research was conducted using a sample of the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2019-2021. This study aims to determine the simultaneous and partial effects of market ratios (earnings per share, price-earnings ratio, dividend yield) and market information (market capitalization and trading volume) on stock returns in food and beverage sub-sector companies, which play an important role in economic growth. The study utilizes the panel data regression method and a non-probability sampling technique, with a total sample size of 60 data points. The results showed that the variables earnings per share, price-earnings ratio, dividend yield, market capitalization, and trading volume had a simultaneous positive effect on stock returns in the food and beverage sub-sector listed on the IDX for the 2019-2021 period. Partially, the variables earnings per share, price-earnings ratio, market capitalization, and trading volume had a positive effect on stock returns. However, dividend yield had no effect on stock returns.